The establishment of domestic civil aviation: legal aspects - B. P. Eliseev (Научный вестник МГТУ ГА, 2023)
2023 is the centenary anniversary year for the domestic civil aviation. At every stage of the branch development, the legal support of its activity was supplemented and transformed which was caused with the specific historical realities. There are few publications dedicated to the early days of the air law as a separate area of legislation. The article presents the historicalretrospective of regulatory regime development throughout the first decades of the aviation industry existence. It is noted, that the first legal act concerning domestic aeronautical industry was published in the late XVIIIth century by Empress Catherine the Great, who was worried about the poor reliability of aerostatic balloons. Later, decrees were published during the reigns of Emperors Alexander I of Russia and Nicholas II of Russia, the latter being the patron of the development of aeronautics. The early Soviet days brought into life the legally relevant resolutions for the development of domestic aviation. Among them, the Resolution of the USSR Council of Labor and Defense dated from February 9th, 1923, about establishing the Council for Civil Aviation at the Main Directorate of the Workers and Peasants’ Red Air Fleet became the crucial milestone. Hence, it is generally accepted that this day is the official date of birth of the country’s civil aviation as an independent branch of the economy. The legal acts of the 20s-40s touched upon the issues of scheduled air transportation, the foundation of the first national airline Dobrolyot, the air traffic control service coordination, the labor and payment provisions for the aviation personnel. The regulatory acts of the pre-war period are logical and laconic, with clear and comprehensive legal language. The pre-revolutionary period archaic style is no longer in use. The legal sources conform to hierarchy and subordination principles. The document content is intended to increase the aircraft and equipment, airspace and flight safety efficiency. During the Great Patriotic War, the «Statute Concerning the Main Directorate of the Civil Air Fleet during the War Time» of the 23rd of June 1941, established by the Council of People’s Commissars of the USSR activated the call-up plans, the manpower of the civil air fleet was involved in combat missions, with the main effort being concentrated on the all possible help to the battlefront.